Efektivitas Pemberian Gula Aren (Arenga Pinnata) dan Madu (Apis Mellifera) Terhadap Endurance pada Atlet Salotellue Fc - Gunawan, Rahmat Dwijaya; Jalil, Rasyidah; Nasriandi, Nasriandi (Universitas Hamzanwadi, 2025)
The problem of this research is that the level of endurance of the player's body is still lacking because when playing a game the players look easily tired and unfit, the cause can be due to the intake of vitamins that athletes need. The purpose of this study was to examine the effectiveness of giving palm sugar and honey to endurance in athletes. Experimental research design with two groups pretest posttest design. The population in this study were 20-25 years old totaling 20 people. Purposive sampling is a non-random sampling method. The instrument for the dose of honey given is 40 ml of honey in 500 ml of water and for the dose of brown sugar is 21 grams of palm sugar in 250 ml of water solution. Data collection in the study was carried out using observation, skill tests, and documentation methods. Data analysis was carried out by parametric statistics using SPSS 22 software. The result 1 obtained a Sig value. (2-tailed) of 0.000 < 0.05, which means that the administration of palm sugar solution is effective on the endurance of Salotellue FC soccer athletes. Based on pair 2, the Sig (2-tailed) value of 0.000 < 0.05 means that giving honey solution is effective on the endurance of Salotellue FC soccer athletes. It is concluded that the administration of palm sugar and honey solutions has an effect on endurance in Salotellue FC athletes.